Using Microalga Scenedesmus quadricauda for the Improvement of Municipal Wastewater Quality - Qader, Muzhda Qasim; Shek, Yahya Ahmed (Iraqi Journal of Science, 2023)
Microalgae culture is an interesting step in wastewater treatment since it provides a tertiary biotreatment while also producing potentially valuable biomass that may be used for a variety of applications. Microalgae cultures, with their ability to utilize inorganic nitrogen and phosphate for growth, provide an elegant solution to tertiary and quaternary treatments. Scenedesmus quadricauda culture was employed with three different doses, 2g/l, 1g/l, and 0.2g/l, to investigate the impacts of microalgae in wastewater. Standard procedures were used to measure samples for physicochemical parameters such as pH, EC, PO4, NO3, NO2, NH4 and BOD5 every third day for 21 days.  Results showed that a higher dose of 2g.l-1 was the most effective for removing the highest rate of nutrients. It was confirmed by significant differences (p≤0.05) between all doses. Ammonium pass had the highest removal percentage of 97%, followed by NO3 with 95.7%, and BOD5 with a range of 90.3 to 93.5 %. Decreases in nutrients were accompanied by a rise in chlorophyll content, with the greatest biomass of 1.52 mg. l-1 on the 17th day of the experiment. The purpose of this paper is to provide an overview of the methods that microalgae use to bioremediate organic contaminants in aquatic ecosystems.